KAJIAN KEBIJAKAN DALAM MEREKOGNISI MASYARAKAT ADAT - Yumantoko Yumantoko (Forestry Study Program University Of Mataram, 2020)
Indonesia has hundreds of ethnic groups spread evenly to remote corners of the country. They live by their own customary law which is different from one another. Many people call them a minority because the tradition is different from some other communities and faces a tension of interest claims with other parties. Minority communities need affirmations so that they are equal as citizens in general. The form of affirmation is reflected in the rules relating to indigenous peoples. However, from many rules there are still many conflicts. This paper is anxious to see the policies that have been taken by the State in recognizing indigenous peoples and whether they are effective in fulfilling indigenous peoples' rights. The result is recognition of indigenous peoples as seen from the many laws and regulations, especially after the Reformation. On the formality side of the rules, indigenous peoples are already represented in the constitution. The state recognizes and there is an effort to provide protection and empowerment, but in terms of effectiveness, the existing legislation has not been able to reduce conflicts between indigenous peoples and other parties, especially related to customary land claims with certain parties. This means that the rules relating to indigenous peoples are more about quantity than quality. This paper recommends simplifying the rules to accommodate the problems faced by indigenous peoples.